HAMA BELALANG KEMBARA (LOCUSTA MIGRATORIA MANILENSIS MEYEN): FAKTA DAN ANALISIS AWAL LEDAKAN POPULASI DI PROVINSI LAMPUNG - Hamim Sudarsono . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2003)
Migratory locust (Locusta migratoria manilensis Meyen) : Preliminary facts and analyzes on the population outbreaks in Lampung Province. The migratory locust (locally known as belalang kembara), Locusta migratoria manilensis Meyen (Orthoptera: Acrididae), has become a major insect pest in Lampung in recent years since its outbreak in 1998. Thousand hectares of agricultural fields were severely destroyed by the locust populations during the course of the outbreak. Local as well as national government were caught in surprised by the population upsurge with little information and technology available for controlling the pest. First presence of locust population was recorded in Kecamatan Pakuan Ratu in 1990. Area damage in the first year was ca. 60 ha. The population grew steadily over the years and reached its peak in April-May of 1998 when thousands of corn and rice fields were severely damaged. Country roads and fields were filled with millions of locust nymphs. Records of locust attacks during preliminary outbreaks from 1990 to 1998 also indicated that the insect started its outbreak from the same areas during those years, i.e. North Lampung District and northern Tulang Bawang District (two of the outmost northern of Lampung Province). Insect pest control experts were very concerned that the locust has established its populations in the region and could cause significant loss in the upcoming years. Control strategy and techniques based on the insect biology and population dynamics, therefore, should be explored and developed to manage future outbreaks. This paper discusses and analyzes preliminary facts and information on the migratory locust and possible strategies that could be implemented for managing the locust.